When linguists and speakers do not agree: The endangered grammar of verbal art in West Africa - (:unkn) unknown (My University, 2018)
Across Africa, linguistic techniques that are closely associated with traditional genres are vulnerable to changes in traditional habits, and often become extinct long before the language is recognized as endangered. Their loss accounts for the discrepancy between professional linguist's assessment and the speakers' perception of the vitality of the language. The study discusses an array of endangered storytelling strategies accumulated by Wan (Mande; Côte d'Ivoire) in response to the needs of traditional narrative performance. Such strategies include morphosyntactic means that allow the storyteller to manage a complex narrative without resorting to explicit lexical encoding or multiplying the number of sentences.
Keywords: African Research